Tinjauan Hukum Perlindungan Konsumen terhadap Praktik Pengumpulan dan Penggunaan Data Pribadi oleh Pelaku Usaha - Rahmad Adip Rizki Perdana; Abid Aulia Hilmi; Helfira Citra (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Due to the advancement of information technology, businesses are increasingly relying on consumer privacy data as a critical component of their digital operations. However, the process of collecting and using private data by businesses frequently violates consumers' privacy. The purpose of this research is to examine Indonesian legal practices regarding consumer privacy protection in the digital business sector. Yuridis normatif is the method used, which involves examining many laws, such as the Rancangan Undang-Undang Perlindungan Data Pribadi (RUU PDP), the Undang-Undang Perlindungan Konsumen, and the Undang-Undang Informasi dan Transaksi Elektronik (ITE). The study's findings indicate that as of right now, undang-undang does not provide consumers with comprehensive protection.